Unveiling the Dynamics of Women’s Self-Help Groups: Exploring Socio-Economic and Socio-Psychological Factors in Debre Birhan, Ethiopia - Wassie, Nebeyu Yohannes; Abebe, Daniel Tefera (Innovation Journal of Social Sciences and Economic Review, 2024)
The study aimed to address the critical research gap in understanding the effectiveness of Group Dynamics (GD) within Self-Help Groups (SHGs) in the Ethiopian context. Specifically, it sought to examine the extent to which socioeconomic and sociopsychological variables predicted group dynamics and how well these dynamics predicted attitudes among SHG members. A correlational design was employed to investigate the relationships between various variables. A sample of 372 SHG members was selected using simple random sampling. Data analysis included correlation and multiple regression techniques. Assumptions of normality, outliers, and multicollinearity were assessed and met. The results revealed several significant findings. Firstly, attitude, extension contact, socioeconomic profile, and social participation of SHG members were found to have statistically significant positive relationships with Group Dynamics Effectiveness (GDE). Secondly, the regression model including these predictors significantly explained 59.3% of the variance in GDE. Attitude emerged as the strongest predictor, contributing 18.5% uniquely to explaining GDE. Lastly, the socioeconomic profile of SHG members was identified as the weakest predictor, explaining only 0.5% of the unique variance in GDE. The study concluded that there is a significant relationship between various factors such as attitude, extension contact, socioeconomic status, and social participation with the effectiveness of group dynamics within SHGs in Ethiopia. Attitude was highlighted as the most influential factor contributing to GDE, while socioeconomic status had a relatively minimal impact. These findings have important implications for the design and implementation of SHG programs in Ethiopia. Specifically, efforts to enhance attitude and extension contact among SHG members may lead to more effective group dynamics, ultimately improving the overall success and impact of SHG initiatives on socioeconomic development in the region.